Defending the Faith? Assessing the Impact of State Religious Exclusivity on Territorial MID Initiation. Issue 3 (September 2020) - Zellman, Ariel; Fox, Jonathan
Abstract: Interstate conflicts involving religion are commonly argued to be more severe and more protracted than other forms of conflict. Although various arguments have sought to explain religion's apparent contributions to global violence, few consider the foreign policy goals over which religious actors actually fight. This article does so by examining whether religiously-exclusive states tend to militarize interstate territorial disputes (MIDs) over issues of strategic material or identity salience. Insofar as religiously-exclusive states seek to "defend the faith" against internal and external challengers, identity-salient disputes should be a particularly attractive target for militarization. We however find the opposite. Although religiously-exclusive states do initiate territorial MIDs more frequently than their secular counterparts, they are significantly more likely to do so owing to disputed territories' strategic rather than symbolic value. These results challenge accepted wisdom regarding religion's influence on international conflict and suggest critical new avenues for research.